Translating passive revolution in Brazil - Roio, Marcos Del [UNESP] (SAGE Publications, 2012)
This article sets out to examine Antonio Gramsci's use of the concept of passive revolution and thereby 'translate' it to an alternative historical and contemporary context. If we can observe Gramsci as a 'translator' of Lenin, from Russia to Italy, we can also try to 'translate' Gramsci beyond his original circumstances to alternative conditions, hence the aim of translating Gramsci and his category of passive revolution in order to apprehend some aspects of the particularity of bourgeois revolution in Brazil. The thesis is that the theory and condition of passive revolution in Brazil has unfolded as a hybridism of liberal corporatism, which reveals the slow assumption of bourgeois rule as a form of supremacy. Importantly, the role of the military in this long process is also highlighted. © The Author(s) 2012.
Keywords: bourgeois revolution; Brazil; corporativism; Passive revolution